2018
DOI: 10.2147/tcrm.s163190
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa/carbidopa/entacapone versus levodopa/dopa-decarboxyiase inhibitor for the treatment of Parkinson's disease: systematic review, meta-analysis, and economic evaluation

Abstract: AimsTo review the evidence for efficacy, safety, and cost-effectiveness of levodopa/carbidopa/entacapone (LCE) compared with levodopa/dopa-decarboxyiase inhibitor (DDCI) for Parkinson’s disease (PD).MethodsPubMed, Embase, the Cochrane Library, and Chinese databases WangFang Data, Chinese Sci-tech Journals Database and China National Knowledge Infrastructure, as well as ClinicalTrials.gov, were searched for randomized controlled trials with “levodopa/carbidopa/entacapone” as keywords. The search period was from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…The Catecholamine-O-Methyltransferase inhibitors (COMT inhibitors) entacapone, tolcapone, and opicapone are given in addition to levodopa in cases of motor fluctuations. In combination with decarboxylase inhibitors, they decrease off-time and in particular reduce off-time compared to levodopa/decarboxylase inhibitors and placebo (Brooks, Sagar, and UK-Irish Entacapone Study Group 2003; Lees et al 2007 ; Lees et al 2017 ; Truong 2009 ; Ferreira et al 2016 ; Yi et al 2018 ). Typical reasons for discontinuation with entacapone are: dyskinesia, diarrhea, discolouration of the urine, nausea, and insufficient effect (Parashos et al 2004 ).…”
Section: Comt Inhibitorsmentioning
confidence: 99%
“…The Catecholamine-O-Methyltransferase inhibitors (COMT inhibitors) entacapone, tolcapone, and opicapone are given in addition to levodopa in cases of motor fluctuations. In combination with decarboxylase inhibitors, they decrease off-time and in particular reduce off-time compared to levodopa/decarboxylase inhibitors and placebo (Brooks, Sagar, and UK-Irish Entacapone Study Group 2003; Lees et al 2007 ; Lees et al 2017 ; Truong 2009 ; Ferreira et al 2016 ; Yi et al 2018 ). Typical reasons for discontinuation with entacapone are: dyskinesia, diarrhea, discolouration of the urine, nausea, and insufficient effect (Parashos et al 2004 ).…”
Section: Comt Inhibitorsmentioning
confidence: 99%
“…Entacapone is a reversible peripheric inhibitor of Catechol-O-methyl transferase that increases the half time effect of levodopa on the motor symptoms. Studies have shown that combination therapy with levodopa/carbidopa/entacapone has a superior efficacy and a safer profile in the treatment of Parkinson's disease patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Antiparkinsonian medication is an essential therapeutic strategy for patients with PD [ 9 , 10 ]. Poor adherence to antiparkinsonian drugs (APDs) may not only reduce patients’ quality of life but also predispose them to complications associated with PD, thereby increasing mortality risk [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%